Synthesis of (±)-Phyltetralin by Cu/Pd-Catalyzed Arylboration - Trammel, Grace L.; Kerlin, Abby C.; Zachau, Christian; Brown, M. Kevin (Synlett, 2023)
A synthesis of (±)-phyltetralin is reported. Notable features of the synthesis include a diastereoselective Cu/Pd-catalyzed arylboration reaction and a Matteson homologation.
Keywords: copper; palladium; boron; arylboration; alkene